2019
DOI: 10.3390/ani9110928
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Faecal versus Rumen Inocula for the Estimation of NDF Digestibility

Abstract: Simple SummaryThe evaluation of fibre digestibility is very important for the formulation of ruminant diets. Fibre digestibility is usually determined in lab with rumen inoculum obtained from cannulated cows. The research of alternative and less invasive inoculum sources is a critical issue that should be addressed. The present study evaluated the potential of faecal inocula, obtained from cows fed different diets, to assess fibre digestibility of different substrates at different incubation times (48, 240 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, a prior adaptation of ruminal microorganisms to this compound is possible, so its degradability is significant. As observed in Chiaravalli et al [43] and Kilama et al [56], lignin is the most important component of NDF or non-degradable NDF that can affect the digestibility of the dry matter or organic matter of foods used in feeding ruminants.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, a prior adaptation of ruminal microorganisms to this compound is possible, so its degradability is significant. As observed in Chiaravalli et al [43] and Kilama et al [56], lignin is the most important component of NDF or non-degradable NDF that can affect the digestibility of the dry matter or organic matter of foods used in feeding ruminants.…”
Section: Discussionmentioning
confidence: 85%
“…The quality and source of the ruminal inoculum directly influence the in vitro evaluation of feed for cattle. The inoculum can be significantly affected by the feed offered to the animals, which can result in differences in the populations of microorganisms in the rumen [18,[42][43][44]. This variation affects the digestibility of the nutritional components of the diet.…”
Section: Discussionmentioning
confidence: 99%
“… Hughes et al (2012) determined that bovine feces included at a rate of 450 g/L of bicarbonate buffer was similar to rumen fluid in the estimate of organic matter digestibility coefficients for tropical forages. Chiaravalli et al (2019) , found that fecal inoculum from dairy cows underpredicted NDF disappearance, primarily when incubations were carried out beyond 288 h for the determination of iNDF. It should be noted, however, that the fecal inoculum to buffer ratio was 1:2 in that instance, well under the 45% recommended by Hughes et al (2012) .…”
Section: Yr Later: What Progress Has Been Made Since 1993?mentioning
confidence: 99%
“…Bovine FF may be used to replace bovine RF for incubation times no lower than 48 h [59]. Chiaravalli et al [60] utilised an AD II incubator to estimate the undigestible NDF of seven substrates using three different inocula (one rumen and two faeces) and considering two incubation times (240 and 360 h). The undigestible NDF results showed that faecal inoculum could be used to replace RF for long incubation times and that faeces can be used as an inoculum for end-point measurements.…”
Section: Faecal Inoculamentioning
confidence: 99%